Performance of evaporator collector and air collector in a solar assisted heat pump dryer - Rahman, S. M. A.; Hawlader, Mohammad Nurul Alam (IIUM Press, 2011)
A solar assisted heat pump dryer has been designed, fabricated and tested. This paper presents the performance of evaporator-collector and air collector, when operated under same meteorological conditions. ASHRAE standard procedure of collector testing has been followed. The absorber platce of the evaporator-collector is made of copper plate painted black without any glazing. At the bottom of the absorber plate, a tube has been soldered in serpentine form. Areas of the evaporator-collector and air collector are 1.5 m2 and 1.24 m2, respectively. The evaporator-collector of the heat pump is acting directly as the solar collector and the temperature of refrigerant at the inlet to the evaporator-collector always remained below the ambient temperature. Due to rejection of sensible and latent heat of air at the dehumidifier. the temperature at the inlet to the air collector is lower than the ambient air. Hence, the thermal efficieney of the air collector also increases due to a reduction of losses from the collector. The efficiency of evaporator-collector and air collector varied between 0.8 - 0.86 and 0.7 - 0.75, respectively.